Drivers and enablers of green purchasing adoption: An empirical investigation of retail hypermarkets in UAE - Akhtar, Pervez (International Journal of Management and Sustainability, 2023)
Growing pressures from various directions have caused managers in the UAE’s retail sector to initiate the use of environmentally friendly approaches such as green purchasing (GP). Expanding on prior work by examining general GP practices, this study explores the GP drivers/enablers that motivate firms in the UAE to adopt GP practices. The results show that retail firms in the selected sectors respond strongly to institutional pressures to adopt GP practices with a beta value of 0.54, customer pressures with a beta value of 0.27, and expected business benefits with a beta value of 0.37. Evidence of a positive relationship between management support and firms’ willingness to take on GP initiatives was weak, so the first hypothesis was not supported with a usual cut-off p-value of 0.05; however, by applying a cut-off p-value of 0.10 or above, it appears that all latent variables suggested in this study have a positive impact on the adoption of GP initiatives among retail hypermarkets in the UAE. This study had three main limitations. First, the sample was drawn from a specific government source, so it may not be a truly comprehensive representation of all retail firms. Second, the small number of samples might have led to bias. Third, as each questionnaire was answered by a single respondent, a common method variance may have resulted. This study will aid firms, as well as the government, who wish to improve their environmental performance in the value chain.